2013
DOI: 10.1007/s10535-013-0332-2
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of loci determining pre-harvest sprouting and dormancy in wheat and barley applying segregation and association mapping

Abstract: Three wheat and two barley populations were studied in order to find loci responsible for dormancy and pre-harvest sprouting. A classical quantitative trait loci analysis was combined with an association mapping approach. Many quantitative trait loci and marker trait associations could be detected on all seven chromosome groups of wheat and on the chromosomes 2H, 3H, 5H, 6H, and 7H of barley. Especially, the known regions on chromosomes 3A and 4A for wheat and 5H for barley were confirmed. Putative functions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…As with the red seed coat genes of the group three chromosomes, one may hypothesize the overlap as being related in function. Lohwasser et al (2013) also reported dormancy QTL QD20.ipk-1D on chromosome 1D just 2.2 cM from QPhs.spa-1D. The minor effect QPhs.spa-1A1 QTL at cfa2135 coincides with a QTL reported by Knox et al (2012) and Jaiswal et al (2012), and is near to QTL reported in many other studies (Glein et al 2006;Munkvold et al 2009;Mohan et al 2009;Singh et al 2010;Rehman et al 2012;Singh et al 2014).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As with the red seed coat genes of the group three chromosomes, one may hypothesize the overlap as being related in function. Lohwasser et al (2013) also reported dormancy QTL QD20.ipk-1D on chromosome 1D just 2.2 cM from QPhs.spa-1D. The minor effect QPhs.spa-1A1 QTL at cfa2135 coincides with a QTL reported by Knox et al (2012) and Jaiswal et al (2012), and is near to QTL reported in many other studies (Glein et al 2006;Munkvold et al 2009;Mohan et al 2009;Singh et al 2010;Rehman et al 2012;Singh et al 2014).…”
Section: Discussionsupporting
confidence: 72%
“…Chromosomes of homoeologous group 4 are considered to have an effective role in pre-harvest sprouting resistance in wheat through dormancy control [Kulwal et al 2010 (review);Lohwasser et al 2013]. Noda et al (2002) investigated another ABA responsive gene located on the long arm of chromosome 4A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By linkage mapping analysis, four were validated as major dormancy loci on 4H, 5H, and 7H (Han et al, 1996). The QTLs in the centromere (SD1) and in the telomeric region of the long arm (SD2) of 5H are considered as the most important dormancy QTLs (Lohwasser, Arif, & Börner, 2013;Romagosa, Han, Clancy, & Ullrich, 1999;Sato, Matsumoto, Ooe, & Takeda, 2009 3) is directly located at this telomeric region in barley. MKK3 is a key signalling module for plant growth and development processes (Xu & Zhang, 2015) and was identified as a strong candidate for barley seed dormancy (Nakamura et al, 2016) and for PHS in an orthologue region of the wheat chromosome 4A (Torada et al, 2016).…”
Section: Marker-trait Associationsmentioning
confidence: 99%
“…Therefore, grain dormancy is deterrent to preharvest sprouting (PHS) and the level of grain dormancy can be used for the assessment of PHS tolerance (Rehman-Arif et al 2012;Lohwasser et al 2013). Grain colour of wheat, influence the flour brightness by contaminating the red pigment in the milling process (Warner et al 2000;Groos et al 2002;Himi et al 2002).…”
Section: Introductionmentioning
confidence: 99%